Case Report: Evolution of KIT D816V-Positive Systemic Mastocytosis to Myeloid Neoplasm With PDGFRA Rearrangement Responsive to Imatinib - Sciumè, Mariarita; Ceparano, Giusy; Eller-Vainicher, Cristina; Fabris, Sonia; Lonati, Silvia; Croci, Giorgio Alberto; Baldini, Luca; Grifoni, Federica Irene (Frontiers in Oncology, 2021)
Systemic mastocytosis (SM) is a rare neoplasm resulting from extracutaneous infiltration of clonal mast cells (MC). Clinical features of SM are very heterogenous and treatment should be highly individualized. Up to 40% of all SM cases can be associated with another hematological neoplasm, most frequently myeloproliferative neoplasms. Here, we present a patient with indolent SM who subsequently developed a myeloid neoplasm with PDGFRA rearrangement with complete response to low-dose imatinib. The 63-year-old patient presented with eosinophilia and elevated serum tryptase level. Bone marrow analysis revealed aberrant MCs in aggregates co-expressing CD2/CD25 and KIT D816V mutation (0.01%), FIP1L1-PDGFRA fusion gene was not identified. In absence of ‘B’ and ‘C’ findings, we diagnosed an indolent form of SM. After 2 years from diagnosis, absolute eosinophil count progressively increased. Bone marrow evaluation showed myeloid hyperplasia and FIP1L1-PDGFRA fusion gene was detected. Thus, the diagnosis of myeloid neoplasm with PDGFRA rearrangement was established. The patient was treated with imatinib 100 mg daily and rapidly obtained a complete molecular remission. Clinical, biological and therapeutic aspects of SM might be challenging, especially when another associated hematological disease is diagnosed. Little is known about the underlying molecular and immunological mechanisms that can promote one entity prevailing over the other one. Currently, the preferred concept of SM pathogenesis is a multimutated neoplasm in which KIT mutations represent a “phenotype modifier” toward SM. Our patient showed an evolution from KIT mutated indolent SM to a myeloid neoplasm with PDGFRA rearrangement; when the eosinophilic component expanded, a regression of the MC counterpart was observed. In conclusion, an extensive clinical monitoring associated with molecular testing is essential to better define these rare diseases and consequently their prognosis and treatment.